Chronological Effects of Rifampicin Discontinuation on Cytochrome P450 Activity in Healthy Japanese Volunteers, Using the Cocktail Method. Issue 6 (23rd August 2013) - Inui, N; Akamatsu, T; Uchida, S; Tanaka, S; Namiki, N; Karayama, M; Chida, K; Watanabe, H
<x xml:space="preserve">Abstract</x> Cytochrome P450 (CYP) 1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A are major factors involved in the metabolism of clinically prescribed drugs. Because the time course after drug treatment discontinuation has received little attention, we aimed to clarify the chronological changes of rifampicin‐induced CYP enzyme activities after rifampicin discontinuation. Thirteen volunteers took 450 mg of rifampicin once daily, and the cocktail method, which uses caffeine, losartan, omeprazole, dextromethorphan, and midazolam as CYP‐specific probes, was repeatedly used for the evaluation of CYP levels. Concentrations of probes and metabolites were determined by liquid chromatography–tandem mass spectrometry. Seven‐day rifampicin administration increased CYP2C19 and CYP3A enzyme activities. The induced CYP2C19 and CYP3A activities remained elevated at 4 days after rifampicin discontinuation and returned to baseline levels 8 days after rifampicin discontinuation. CYP1A2 and CYP2D6 enzyme activities showed no significant changes, and CYP2C9 enzyme activity was increased with rifampicin administration, with a tendency toward statistical significance. Drug interactions can occur even after rifampicin discontinuation. Clinical Pharmacology & Therapeutics (2013); 94 6, 702–708. doi:10.1038/clpt.2013.167